Thermo-mechanical improvement of Inconel 718 using ex situ boron nitride-reinforced composites processed by laser powder bed fusion. Issue 1 (December 2017) - Kim, Sang; Shin, Gi-Hun; Kim, Byoung-Kee; Kim, Kyung; Yang, Dong-Yeol; Aranas, Clodualdo; Choi, Joon-Phil; Yu, Ji-Hun
Abstract Hexagonal boron nitride-reinforced Inconel 718 (h-BN/IN718) composites were fabricated using a laser powder bed fusion (LPBF) technique to treat a nanosheet-micropowder precursor mixture prepared in a mechanical blending process. Tailoring the BN in IN718 enhanced the thermal resistance of the composites, thereby dampening the sharpness of the melting temperature peak at 1364 °C. This is because the presence of the BN reinforcement, which has a low coefficient of thermal expansion (CTE), resulted in a heat-blocking effect within the matrix. Following this lead, we found that the BN (2.29 g/cm3 ) was uniformly distributed and strongly embedded in the IN718 (8.12 g/cm3 ), with the lowest alloy density value (7.03 g/cm3 ) being obtained after the addition of 12 vol% BN. Consequently, its specific hardness and compressive strength rose to 41.7 Hv0.5 · cm3 /g and 92.4 MPa· cm3 /g, respectively, compared to the unreinforced IN718 alloy with 38.7 Hv0.5 · cm3 /g and 89.4 MPa· cm3 /g, respectively. Most importantly, we discovered that the wear resistance of the composite improved compared to the unreinforced IN718, indicated by a decrease in the coefficient of friction (COF) from 0.43 to 0.31 at 2400 s. This is because the BN has an exfoliated surface and intrinsically high sliding and lubricating characteristics.